The Relationship between Macroeconomics and the Jakarta Composite Index (JCI) in Bearish Conditions during COVID-19 - Aini, Yulis Nurul; Evelina, Tri Yulistyawati; Alabdullah, Tariq Tawfeeq Yousif; Sulasari, Ayu; Trianti, Khoiriyah (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The purpose of this research is to investigate how macroeconomic factors influence the Composite Stock Price Index (JCI) in times of market decline due to the COVID-19 pandemic. Information for this study will be gathered from official sources such as the Indonesia Stock Exchange, the Central Bureau of Statistics, and Bank Indonesia. The information analyzed consists of monthly data on the Composite Stock Price Index, inflation, and interest rates.   Multiple regression is the method employed in this study. The findings show that inflation has a notable positive impact on the Composite Stock Price Index, causing bearish trends during the COVID-19 pandemic, while interest rates have a significant negative impact, resulting in bullish trends during the COVID-19 pandemic.